Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

Dysfunction of the ciliary ARMC9/TOGARAM1 protein module causes Joubert syndrome. - Latour, Brooke L; Van De Weghe, Julie C; Rusterholz, Tamara Ds; Letteboer, Stef Jf; Gomez, Arianna; Shaheen, Ranad; Gesemann, Matthias; Karamzade, Arezou; Asadollahi, Mostafa; Barroso-Gil, Miguel; Chitre, Manali; Grout, Megan E; et al. (J Clin Invest, 2020)
Joubert syndrome (JBTS) is a recessive neurodevelopmental ciliopathy characterized by a pathognomonic hindbrain malformation. All known JBTS genes encode proteins involved in the structure or function of primary cilia, ubiquitous antenna-like organelles essential for cellular signal transduction. Here, we used the recently identified JBTS-associated protein armadillo repeat motif-containing 9 (ARMC9) in tandem-affinity purification and yeast 2-hybrid screens to identify a ciliary module whose dysfunction underlies JBTS. In addition to the known JBTS-associated proteins CEP104 and CSPP1, we identified coiled-coil domain containing 66 (CCDC66) and TOG array regulator of axonemal microtubules 1 (TOGARAM1) as ARMC9 interaction partners. We found that TOGARAM1 variants cause JBTS and disrupt TOGARAM1 interaction with ARMC9. Using a combination of protein interaction analyses, characterization of patient-derived fibroblasts, and analysis of CRISPR/Cas9-engineered zebrafish and hTERT-RPE1 cells, we demonstrated that dysfunction of ARMC9 or TOGARAM1 resulted in short cilia with decreased axonemal acetylation and polyglutamylation, but relatively intact transition zone function. Aberrant serum-induced ciliary resorption and cold-induced depolymerization in ARMC9 and TOGARAM1 patient cell lines suggest a role for this new JBTS-associated protein module in ciliary stability.
Keywords: Abnormalities, Multiple; Acetylation; Animals; Armadillo Domain Proteins; Cerebellum; Cilia; CRISPR-Cas Systems; Disease Models, Animal; Eye Abnormalities; Humans; Kidney Diseases, Cystic; Peptides; Retina; Zebrafish; Zebrafish Proteins

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gomez-López-Hernández syndrome: A case report with clinical and molecular evaluation and literature review. - Perrone, Eduardo; D'Almeida, Vânia; de Macena Sobreira, Nara Lygia; de Mello, Claudia Berlim; de Oliveira, Allan Chiaratti; Burlin, Stênio; Soares, Maria de Fátima de Faria; Cernach, Mirlene Cecília Soares Pinho; Alvarez Perez, Ana Beatriz (Am J Med Genet A, 2020)
Gomez-López-Hernández syndrome (GLHS) is characterized by rhombencephalosynapsis (RES), alopecia, trigeminal anesthesia and a distinctive phenotype, including brachyturricephaly. It has been suggested that GLHS should be considered as part of the spectrum of RES-associated conditions that include alopecia, trigeminal anesthesia, and craniofacial anomalies, rather than a distinct entity. To the best of our knowledge, 57 patients with GLHS have been described. Despite its first description in 1979, the etiology of this syndrome remains unknown. Here, we describe, to our knowledge, the first case of a patient with GLHS who was molecularly evaluated and had been prenatally exposed to misoprostol. We also reviewed the clinical and morphological features of the patients described to date to better delineate the phenotype and focus on any evidence for adverse pregnancy outcomes or exposure, including teratogens.
Keywords: Abnormalities, Multiple; Alopecia; Cerebellum; Child; Child, Preschool; Craniofacial Abnormalities; Female; Growth Disorders; Humans; Magnetic Resonance Imaging; Misoprostol; Neurocutaneous Syndromes; Phenotype; Rhombencephalon; Trigeminal Nerve

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Prenatal Diagnosis of a Ventral Abdominal Wall Defect. - Beam, Kristyn; Wojcik, Monica H; Agrawal, Pankaj B; Smithers, Charles; Estroff, Judy (Neoreviews, 2020)
Keywords: Abnormalities, Multiple; Echocardiography; Fatal Outcome; Female; Hernia, Abdominal; Hernia, Diaphragmatic; Hernia, Ventral; Humans; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prenatal Diagnosis; Ultrasonography, Prenatal

De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism. - Zawerton, Ash; Yao, Baojin; Yeager, J Paige; Pippucci, Tommaso; Haseeb, Abdul; Smith, Joshua D; Wischmann, Lisa; Kühl, Susanne J; Dean, John C S; Pilz, Daniela T; Holder, Susan E; McNeill, Alisdair; et al. (Am J Hum Genet, 2019)
SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share developmental delay, intellectual disability, and mild facial and digital morphological abnormalities. SOX4 is highly expressed in areas of active neurogenesis in human fetuses, and sox4 knockdown in Xenopus embryos diminishes brain and whole-body size. The SOX4 variants cluster in the highly conserved, SOX family-specific HMG domain, but each alters a different residue. In silico tools predict that each variant affects a distinct structural feature of this DNA-binding domain, and functional assays demonstrate that these SOX4 proteins carrying these variants are unable to bind DNA in vitro and transactivate SOX reporter genes in cultured cells. These variants are not found in the gnomAD database of individuals with presumably normal development, but 12 other SOX4 HMG-domain missense variants are recorded and all demonstrate partial to full activity in the reporter assay. Taken together, these findings point to specific SOX4 HMG-domain missense variants as the cause of a characteristic human neurodevelopmental disorder associated with mild facial and digital dysmorphism.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Child; Child, Preschool; Coffin-Lowry Syndrome; Cohort Studies; Conserved Sequence; DNA; Female; Heterozygote; HMG-Box Domains; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; SOXC Transcription Factors; Transcriptional Activation; Xenopus

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Muzny, Donna M; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Signal Transduction

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Microcephaly; Micrognathism; Mutation; Neck; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van Ijcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder

Mutations in ARMC9, which Encodes a Basal Body Protein, Cause Joubert Syndrome in Humans and Ciliopathy Phenotypes in Zebrafish. - Van De Weghe, Julie C; Rusterholz, Tamara D S; Latour, Brooke; Grout, Megan E; Aldinger, Kimberly A; Shaheen, Ranad; Dempsey, Jennifer C; Maddirevula, Sateesh; Cheng, Yong-Han H; Phelps, Ian G; Gesemann, Matthias; Goel, Himanshu; et al. (Am J Hum Genet, 2017)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by hypotonia, ataxia, abnormal eye movements, and variable cognitive impairment. It is defined by a distinctive brain malformation known as the "molar tooth sign" on axial MRI. Subsets of affected individuals have malformations such as coloboma, polydactyly, and encephalocele, as well as progressive retinal dystrophy, fibrocystic kidney disease, and liver fibrosis. More than 35 genes have been associated with JS, but in a subset of families the genetic cause remains unknown. All of the gene products localize in and around the primary cilium, making JS a canonical ciliopathy. Ciliopathies are unified by their overlapping clinical features and underlying mechanisms involving ciliary dysfunction. In this work, we identify biallelic rare, predicted-deleterious ARMC9 variants (stop-gain, missense, splice-site, and single-exon deletion) in 11 individuals with JS from 8 families, accounting for approximately 1% of the disorder. The associated phenotypes range from isolated neurological involvement to JS with retinal dystrophy, additional brain abnormalities (e.g., heterotopia, Dandy-Walker malformation), pituitary insufficiency, and/or synpolydactyly. We show that ARMC9 localizes to the basal body of the cilium and is upregulated during ciliogenesis. Typical ciliopathy phenotypes (curved body shape, retinal dystrophy, coloboma, and decreased cilia) in a CRISPR/Cas9-engineered zebrafish mutant model provide additional support for ARMC9 as a ciliopathy-associated gene. Identifying ARMC9 mutations as a cause of JS takes us one step closer to a full genetic understanding of this important disorder and enables future functional work to define the central biological mechanisms underlying JS and other ciliopathies.
Keywords: Abnormalities, Multiple; Animals; Armadillo Domain Proteins; Basal Bodies; Base Sequence; Brain; Cerebellum; Cilia; Ciliopathies; Diagnostic Imaging; Exome; Eye Abnormalities; Genetic Predisposition to Disease; Humans; Kidney Diseases, Cystic; Mutation; Phenotype; Retina; Sequence Analysis, DNA; Up-Regulation; Zebrafish; Zebrafish Proteins

A novel mutation in GMPPA in siblings with apparent intellectual disability, epilepsy, dysmorphism, and autonomic dysfunction. - Gold, Wendy A; Sobreira, Nara; Wiame, Elsa; Marbaix, Alexandre; Van Schaftingen, Emile; Franzka, Patricia; Riley, Lisa G; Worgan, Lisa; Hübner, Christian A; Christodoulou, John; Adès, Lesley C (Am J Med Genet A, 2017)
GMPPA encodes the GDP-mannose pyrophosphorylase A protein (GMPPA). The function of GMPPA is not well defined, however it is a homolog of GMPPB which catalyzes the reaction that converts mannose-1-phosphate and guanosine-5'-triphosphate to GDP-mannose. Previously, biallelic mutations in GMPPA were reported to cause a disorder characterized by achalasia, alacrima, neurological deficits, and intellectual disability. In this study, we report a female proband with achalasia, alacrima, hypohydrosis, apparent intellectual disability, seizures, microcephaly, esotropia, and craniofacial dysmorphism. Exome sequencing identified a previously unreported homozygous c.853+1G>A variant in GMPPA in the proband and her affected sister. Their unaffected parents were heterozygous, and unaffected brother homozygous wild type for this variant. Lymphoblast cells from the affected sisters showed complete loss of the GMPPA protein by Western blotting, and increased levels of GDP-mannose in lymphoblasts on high performance liquid chromatography. Based on our findings and the previous report describing patients with an overlapping phenotype, we conclude that this novel variant in GMPPA, identified by exome sequencing in the proband and her affected sister, is the genetic cause of their phenotype and may expand the known phenotype of this recently described glycosylation disorder.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; Craniofacial Abnormalities; Epilepsy; Exome; Facies; Female; Heterozygote; Humans; Intellectual Disability; Microcephaly; Muscular Atrophy; Mutation, Missense; Nucleotidyltransferases; Pedigree; Phenotype; Seizures

Patients with a Kabuki syndrome phenotype demonstrate DNA methylation abnormalities. - Sobreira, Nara; Brucato, Martha; Zhang, Li; Ladd-Acosta, Christine; Ongaco, Chrissie; Romm, Jane; Doheny, Kimberly F; Mingroni-Netto, Regina C; Bertola, Débora; Kim, Chong A; Perez, Ana Ba; Melaragno, Maria I; et al. (Eur J Hum Genet, 2017)
Kabuki syndrome is a monogenic disorder caused by loss of function variants in either of two genes encoding histone-modifying enzymes. We performed targeted sequencing in a cohort of 27 probands with a clinical diagnosis of Kabuki syndrome. Of these, 12 had causative variants in the two known Kabuki syndrome genes. In 2, we identified presumptive loss of function de novo variants in KMT2A (missense and splice site variants), a gene that encodes another histone modifying enzyme previously exclusively associated with Wiedermann-Steiner syndrome. Although Kabuki syndrome is a disorder of histone modification, we also find alterations in DNA methylation among individuals with a Kabuki syndrome diagnosis relative to matched normal controls, regardless of whether they carry a variant in KMT2A or KMT2D or not. Furthermore, we observed characteristic global abnormalities of DNA methylation that distinguished patients with a loss of function variant in KMT2D or missense or splice site variants in either KMT2D or KMT2A from normal controls. Our results provide new insights into the relationship of genotype to epigenotype and phenotype and indicate cross-talk between histone and DNA methylation machineries exposed by inborn errors of the epigenetic apparatus.
Keywords: Abnormalities, Multiple; Case-Control Studies; Child; DNA Methylation; Face; Female; Hematologic Diseases; Histone-Lysine N-Methyltransferase; Humans; Loss of Function Mutation; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Vestibular Diseases

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Congenital nephrotic syndrome in an infant with ALG1-congenital disorder of glycosylation. - Harshman, Lyndsay A; Ng, Bobby G; Freeze, Hudson H; Trapane, Pamela; Dolezal, Anna; Brophy, Patrick D; Brumbaugh, Jane E (Pediatr Int, 2016)
Congenital nephrotic syndrome (NS) in the newborn is most frequently related to mutations in genes specific for structural integrity of the glomerular basement membrane and associated filtration structures within the kidney, resulting in massive leakage of plasma proteins into the urine. Occurrence of congenital NS in a multi-system syndrome is less common. We describe the case of an infant with deteriorating neurological status, seizures, edema, and proteinuria who was found to have a mutation in gene ALG1 and a renal biopsy consistent with congenital NS. Furthermore, we briefly review rare existing case reports documenting congenital NS in patients with mutations in ALG1, and treatment strategies, including novel use of peritoneal dialysis.
Keywords: Abnormalities, Multiple; Congenital Disorders of Glycosylation; DNA; DNA Mutational Analysis; Glycosylation; Humans; Infant, Newborn; Male; Mannosyltransferases; Mutation; Nephrotic Syndrome; Peritoneal Dialysis

Exome sequencing identifies a de novo frameshift mutation in the imprinted gene ZDBF2 in a sporadic patient with Nasopalpebral Lipoma-coloboma syndrome. - Chacón-Camacho, Oscar F; Sobreira, Nara; You, Jing; Piña-Aguilar, Raul E; Villegas-Ruiz, Vanessa; Zenteno, Juan C (Am J Med Genet A, 2016)
Nasopalpebral lipoma-coloboma syndrome (NPLCS, OMIM%167730) is an uncommon malformation entity with autosomal dominant inheritance characterized by the combination of nasopalpebral lipoma, colobomas in upper and lower eyelids, telecanthus, and maxillary hypoplasia. To date, no genetic defects have been associated with familial or sporadic NPLCS cases and the etiology of the disease remains unknown. In this work, the results of whole exome sequencing in a sporadic NPLCS patient are presented. Exome sequencing identified a de novo heterozygous frameshift dinucleotide insertion c.6245_6246 insTT (p.His2082fs*67) in ZDBF2 (zinc finger, DBF-type containing 2), a gene located at 2q33.3. This variant was absent in parental DNA, in a set of 300 ethnically matched controls, and in public exome variant databases. This is the first genetic variant identified in a NPLCS patient and evidence supporting the pathogenicity of the identified mutation is discussed. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Base Sequence; Child, Preschool; Coloboma; DNA-Binding Proteins; Exome; Eyelid Neoplasms; Female; Frameshift Mutation; Genomic Imprinting; Humans; Lipoma; Pedigree

Gonadal mosaicism in ARID1B gene causes intellectual disability and dysmorphic features in three siblings. - Ben-Salem, Salma; Sobreira, Nara; Akawi, Nadia A; Al-Shamsi, Aisha M; John, Anne; Pramathan, Thachillath; Valle, David; Ali, Bassam R; Al-Gazali, Lihadh (Am J Med Genet A, 2016)
The gene encoding the AT-rich interaction domain-containing protein 1B (ARID1B) has recently been shown to be one of the most frequently mutated genes in patients with intellectual disability (ID). The phenotypic spectrums associated with variants in this gene vary widely ranging for mild to severe non-specific ID to Coffin-Siris syndrome. In this study, we evaluated three children from a consanguineous Emirati family affected with ID and dysmorphic features. Genomic DNA from all affected siblings was analyzed using CGH array and whole-exome sequencing (WES). Based on a recessive mode of inheritance, homozygous or compound heterozygous variants shared among all three affected children could not be identified. However, further analysis revealed a heterozygous variant (c.4318C>T; p.Q1440*) in the three affected children in an autosomal dominant ID causing gene, ARID1B. This variant was absent in peripheral blood samples obtained from both parents and unaffected siblings. Therefore, we propose that the most likely explanation for this situation is that one of the parents is a gonadal mosaic for the variant. To the best of our knowledge, this is the first report of a gonadal mosaicism inheritance of an ARID1B variant leading to familial ID recurrence.
Keywords: Abnormalities, Multiple; Adolescent; Child; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Mosaicism; Mutation; Neck; Pedigree; Siblings; Transcription Factors

An inactivating mutation in intestinal cell kinase, ICK, impairs hedgehog signalling and causes short rib-polydactyly syndrome. - Paige Taylor, S; Kunova Bosakova, Michaela; Varecha, Miroslav; Balek, Lukas; Barta, Tomas; Trantirek, Lukas; Jelinkova, Iva; Duran, Ivan; Vesela, Iva; Forlenza, Kimberly N; Martin, Jorge H; Hampl, Ales; et al. (Hum Mol Genet, 2016)
The short rib polydactyly syndromes (SRPS) are a group of recessively inherited, perinatal-lethal skeletal disorders primarily characterized by short ribs, shortened long bones, varying types of polydactyly and concomitant visceral abnormalities. Mutations in several genes affecting cilia function cause SRPS, revealing a role for cilia function in skeletal development. To identify additional SRPS genes and discover novel ciliary molecules required for normal skeletogenesis, we performed exome sequencing in a cohort of patients and identified homozygosity for a missense mutation, p.E80K, in Intestinal Cell Kinase, ICK, in one SRPS family. The p.E80K mutation abolished serine/threonine kinase activity, resulting in altered ICK subcellular and ciliary localization, increased cilia length, aberrant cartilage growth plate structure, defective Hedgehog and altered ERK signalling. These data identify ICK as an SRPS-associated gene and reveal that abnormalities in signalling pathways contribute to defective skeletogenesis.
Keywords: Abnormalities, Multiple; Cilia; Exome; Female; Hedgehog Proteins; Humans; Infant; MAP Kinase Signaling System; Pedigree; Pregnancy; Protein-Serine-Threonine Kinases; Sequence Analysis, DNA; Short Rib-Polydactyly Syndrome; Signal Transduction; Skeleton

Mutations in CEP120 cause Joubert syndrome as well as complex ciliopathy phenotypes. - Roosing, Susanne; Romani, Marta; Isrie, Mala; Rosti, Rasim Ozgur; Micalizzi, Alessia; Musaev, Damir; Mazza, Tommaso; Al-Gazali, Lihadh; Altunoglu, Umut; Boltshauser, Eugen; D'Arrigo, Stefano; De Keersmaecker, Bart; et al. (J Med Genet, 2016)
BACKGROUND: Ciliopathies are an extensive group of autosomal recessive or X-linked disorders with considerable genetic and clinical overlap, which collectively share multiple organ involvement and may result in lethal or viable phenotypes. In large numbers of cases the genetic defect remains yet to be determined. The aim of this study is to describe the mutational frequency and phenotypic spectrum of the CEP120 gene. METHODS: Exome sequencing was performed in 145 patients with Joubert syndrome (JS), including 15 children with oral-facial-digital syndrome type VI (OFDVI) and 21 Meckel syndrome (MKS) fetuses. Moreover, exome sequencing was performed in one fetus with tectocerebellar dysraphia with occipital encephalocele (TCDOE), molar tooth sign and additional skeletal abnormalities. As a parallel study, 346 probands with a phenotype consistent with JS or related ciliopathies underwent next-generation sequencing-based targeted sequencing of 120 previously described and candidate ciliopathy genes. RESULTS: We present six probands carrying nine distinct mutations (of which eight are novel) in the CEP120 gene, previously found mutated only in Jeune asphyxiating thoracic dystrophy (JATD). The CEP120-associated phenotype ranges from mild classical JS in four patients to more severe conditions in two fetuses, with overlapping features of distinct ciliopathies that include TCDOE, MKS, JATD and OFD syndromes. No obvious correlation is evident between the type or location of identified mutations and the ciliopathy phenotype. CONCLUSION: Our findings broaden the spectrum of phenotypes caused by CEP120 mutations that account for nearly 1% of patients with JS as well as for more complex ciliopathy phenotypes. The lack of clear genotype-phenotype correlation highlights the relevance of comprehensive genetic analyses in the diagnostics of ciliopathies.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Cell Cycle Proteins; Cerebellar Diseases; Cerebellum; Child; Ciliopathies; Encephalocele; Eye Abnormalities; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Humans; Kidney Diseases, Cystic; Male; Mutation; Mutation Rate; Orofaciodigital Syndromes; Pedigree; Phenotype; Retina; Sequence Alignment

Visceral myopathy: Clinical and molecular survey of a cohort of seven new patients and state of the art of overlapping phenotypes. - Moreno, Carolina Araujo; Metze, Konradin; Lomazi, Elizete Aparecida; Bertola, Débora Romeo; Barbosa, Ricardo Henrique Almeida; Cosentino, Viviana; Sobreira, Nara; Cavalcanti, Denise Pontes (Am J Med Genet A, 2016)
Visceral motility dysfunction is a key feature of genetic disorders such as megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS, MIM moved from 249210 to 155310), chronic intestinal pseudo-obstruction (CIPO, MIM609629), and multisystemic smooth muscle dysfunction syndrome (MSMDS, MIM613834). The genetic bases of these conditions recently begun to be clarified with the identification of pathogenic variants in ACTG2, ACTA2, and MYH11 in individuals with visceral motility dysfunction. The MMIHS was associated with the heterozygous variant in ACTG2 and homozygous variant in MYH11, while the heterozygous variant in ACTA2 was observed in patients with MSMDS. In this study, we describe the clinical data as well as the molecular investigation of seven individuals with visceral myopathy phenotypes. Five patients presented with MMIHS, including two siblings from consanguineous parents, one had CIPO, and the other had MSMDS. In three individuals with MMIHS and in one with CIPO we identified heterozygous variant in ACTG2, one being a novel variant (c.584C>T-p.Thr195Ile). In the individual with MSMDS we identified a heterozygous variant in ACTA2. We performed the whole-exome sequencing in one sibling with MMIHS and her parents; however, the pathogenic variant responsible for her phenotype could not be identified. These results reinforce the clinical and genetic heterogeneity of the visceral myopathies. Although many cases of MMIHS are associated with ACTG2 variants, we suggest that other genes, besides MYH11, could cause the MMIHS with autosomal recessive pattern. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Actins; Child, Preschool; Colon; Consanguinity; DNA Mutational Analysis; Fatal Outcome; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Phenotype; Polymorphism, Single Nucleotide; Treatment Outcome; Ultrasonography, Prenatal; Urinary Bladder

Exome sequencing identifies a homozygous C5orf42 variant in a Turkish kindred with oral-facial-digital syndrome type VI. - Bayram, Yavuz; Aydin, Hatip; Gambin, Tomasz; Akdemir, Zeynep Coban; Atik, Mehmed M; Karaca, Ender; Karaman, Ali; Pehlivan, Davut; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Am J Med Genet A, 2015)
Oral-facial-digital syndrome type VI (OFDVI) is a rare ciliopathy in the spectrum of Joubert syndrome (JS) and distinguished from other oral-facial-digital syndromes by metacarpal abnormalities with central polydactyly and by a molar tooth sign on cranial MRI. Additional characteristic features include short stature, micrognathia, posteriorly rotated low-set ears, hypertelorism, epicanthal folds, broad nasal tip, tongue hamartoma, upper lip notch, intraoral frenula, cleft lip/palate, and renal anomalies. Recently, novel mutations in C5orf42 were identified in 9 out of 11 OFDVI families. In a subsequent study C5orf42 was found to be mutated in only 2 out of 17 OFDVI probands while 28 patients with a pure JS phenotype also had pathogenic mutations of C5orf42. We report on two affected cousins diagnosed with OFDVI who were born from first degree cousin marriages. Whole exome sequencing (WES) identified a homozygous predicted damaging missense mutation (c.4034A > G; p.Gln1345Arg) in the C5orf42 gene. Our data contribute to the evidence that C5orf42 is one of the causative genes for OFDVI.
Keywords: Abnormalities, Multiple; Cerebellar Diseases; Cerebellum; Child; Cleft Palate; Exome; Eye Abnormalities; Female; Genetic Predisposition to Disease; Hamartoma; Homozygote; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Male; Membrane Proteins; Middle Aged; Mutation; Orofaciodigital Syndromes; Phenotype; Retina; Turkey

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

GeneMatcher aids in the identification of a new malformation syndrome with intellectual disability, unique facial dysmorphisms, and skeletal and connective tissue abnormalities caused by de novo variants in HNRNPK. - Au, P Y Billie; You, Jing; Caluseriu, Oana; Schwartzentruber, Jeremy; Majewski, Jacek; Bernier, Francois P; Ferguson, Marcia; Valle, David; Parboosingh, Jillian S; Sobreira, Nara; Innes, A Micheil; Kline, Antonie D (Hum Mutat, 2015)
We report a new syndrome due to loss-of-function variants in the heterogeneous nuclear ribonucleoprotein K gene (HNRNPK). We describe two probands: one with a de novo frameshift (NM_002140.3: c.953+1dup), and the other with a de novo splice donor site variant (NM_002140.3: c.257G>A). Both probands have intellectual disability, a shared unique craniofacial phenotype, and connective tissue and skeletal abnormalities. The identification of this syndrome was made possible by a new online tool, GeneMatcher, which facilitates connections between clinicians and researchers based on shared interest in candidate genes. This report demonstrates that new Web-based approaches can be effective in helping investigators solve exome sequencing projects, and also highlights the newer paradigm of "reverse phenotyping," where characterization of syndromic features follows the identification of genetic variants.
Keywords: Abnormalities, Multiple; Adolescent; Child; Craniofacial Abnormalities; Databases, Genetic; Genetic Predisposition to Disease; Heterogeneous-Nuclear Ribonucleoprotein K; Humans; Information Dissemination; Intellectual Disability; Male; Muscular Atrophy; Phenotype; Polymorphism, Single Nucleotide; Ribonucleoproteins; Software; Web Browser

Joubert syndrome: a model for untangling recessive disorders with extreme genetic heterogeneity. - Bachmann-Gagescu, R; Dempsey, J C; Phelps, I G; O'Roak, B J; Knutzen, D M; Rue, T C; Ishak, G E; Isabella, C R; Gorden, N; Adkins, J; Boyle, E A; de Lacy, N; et al. (J Med Genet, 2015)
BACKGROUND: Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterised by hypotonia, ataxia, cognitive impairment, abnormal eye movements, respiratory control disturbances and a distinctive mid-hindbrain malformation. JS demonstrates substantial phenotypic variability and genetic heterogeneity. This study provides a comprehensive view of the current genetic basis, phenotypic range and gene-phenotype associations in JS. METHODS: We sequenced 27 JS-associated genes in 440 affected individuals (375 families) from a cohort of 532 individuals (440 families) with JS, using molecular inversion probe-based targeted capture and next-generation sequencing. Variant pathogenicity was defined using the Combined Annotation Dependent Depletion algorithm with an optimised score cut-off. RESULTS: We identified presumed causal variants in 62% of pedigrees, including the first B9D2 mutations associated with JS. 253 different mutations in 23 genes highlight the extreme genetic heterogeneity of JS. Phenotypic analysis revealed that only 34% of individuals have a 'pure JS' phenotype. Retinal disease is present in 30% of individuals, renal disease in 25%, coloboma in 17%, polydactyly in 15%, liver fibrosis in 14% and encephalocele in 8%. Loss of CEP290 function is associated with retinal dystrophy, while loss of TMEM67 function is associated with liver fibrosis and coloboma, but we observe no clear-cut distinction between JS subtypes. CONCLUSIONS: This work illustrates how combining advanced sequencing techniques with phenotypic data addresses extreme genetic heterogeneity to provide diagnostic and carrier testing, guide medical monitoring for progressive complications, facilitate interpretation of genome-wide sequencing results in individuals with a variety of phenotypes and enable gene-specific treatments in the future.
Keywords: Abnormalities, Multiple; Cerebellum; Cohort Studies; DNA Mutational Analysis; Eye Abnormalities; Genetic Association Studies; Genetic Heterogeneity; Humans; Kidney Diseases, Cystic; Models, Theoretical; Pedigree; Retina; Sequence Analysis, DNA

KIAA0586 is Mutated in Joubert Syndrome. - Bachmann-Gagescu, Ruxandra; Phelps, Ian G; Dempsey, Jennifer C; Sharma, Vivek A; Ishak, Gisele E; Boyle, Evan A; Wilson, Meredith; Marques Lourenço, Charles; Arslan, Mutluay; Shendure, Jay; Doherty, Dan (Hum Mutat, 2015)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by a distinctive mid-hindbrain malformation. JS is part of a group of disorders called ciliopathies based on their overlapping phenotypes and common underlying pathophysiology linked to primary cilium dysfunction. Biallelic mutations in one of 28 genes, all encoding proteins localizing to the primary cilium or basal body, can cause JS. Despite this large number of genes, the genetic cause can currently be determined in about 62% of individuals with JS. To identify novel JS genes, we performed whole exome sequencing on 35 individuals with JS and found biallelic rare deleterious variants (RDVs) in KIAA0586, encoding a centrosomal protein required for ciliogenesis, in one individual. Targeted next-generation sequencing in a large JS cohort identified biallelic RDVs in eight additional families for an estimated prevalence of 2.5% (9/366 JS families). All affected individuals displayed JS phenotypes toward the mild end of the spectrum.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Alternative Splicing; Brain; Cell Cycle Proteins; Cerebellum; Child; Child, Preschool; DNA Mutational Analysis; Eye Abnormalities; Gene Order; Genetic Association Studies; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Mutation; Phenotype; Retina; Young Adult

Mutations in SPATA5 Are Associated with Microcephaly, Intellectual Disability, Seizures, and Hearing Loss. - Tanaka, Akemi J; Cho, Megan T; Millan, Francisca; Juusola, Jane; Retterer, Kyle; Joshi, Charuta; Niyazov, Dmitriy; Garnica, Adolfo; Gratz, Edward; Deardorff, Matthew; Wilkins, Alisha; Ortiz-Gonzalez, Xilma; et al. (Am J Hum Genet, 2015)
Using whole-exome sequencing, we have identified in ten families 14 individuals with microcephaly, developmental delay, intellectual disability, hypotonia, spasticity, seizures, sensorineural hearing loss, cortical visual impairment, and rare autosomal-recessive predicted pathogenic variants in spermatogenesis-associated protein 5 (SPATA5). SPATA5 encodes a ubiquitously expressed member of the ATPase associated with diverse activities (AAA) protein family and is involved in mitochondrial morphogenesis during early spermatogenesis. It might also play a role in post-translational modification during cell differentiation in neuronal development. Mutations in SPATA5 might affect brain development and function, resulting in microcephaly, developmental delay, and intellectual disability.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Base Sequence; Exome; Female; Gene Frequency; Genes, Recessive; Hearing Loss; Homeodomain Proteins; Humans; Intellectual Disability; Male; Microcephaly; Molecular Sequence Data; Mutation; Seizures; Sequence Alignment; Sequence Analysis, DNA

NGLY1 mutation causes neuromotor impairment, intellectual disability, and neuropathy. - Çağlayan, Ahmet Okay; Comu, Sinan; Baranoski, Jacob F; Parman, Yesim; Kaymakçalan, Hande; Akgümüş, Gözde Tuğce; Caglar, Caner; Dölen, Duygu; Erson-Omay, Emine Zeynep; Harmanci, Akdes Serin; Mishra-Gorur, Ketu; Freeze, Hudson H; et al. (Eur J Med Genet, 2015)
N-glycanase 1 (NGLY1) is a conserved enzyme that is responsible for the deglycosylation of misfolded N-glycosylated proteins in the cytoplasm prior to their proteasome-mediated degradation. Disruption of this degradation process has been associated with various neurologic diseases including amyotrophic lateral sclerosis and Parkinson's disease. Here, we describe two siblings with neuromotor impairment, apparent intellectual disability, corneal opacities, and neuropathy who were found to possess a novel homozygous frame-shift mutation due to a 4 base pair deletion in NGLY1 (c.1533_1536delTCAA, p.Asn511LysfsX51). We hypothesize that this mutation likely limits the capability of neuronal cells to respond to stress due to accumulation of misfolded proteins, thereby impairing their survival and resulting in progressive loss of neurological function.
Keywords: Abnormalities, Multiple; Adolescent; Child; Corneal Opacity; Developmental Disabilities; Female; Frameshift Mutation; Genotype; Humans; Intellectual Disability; Male; Movement Disorders; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Peripheral Nervous System Diseases

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Yuan, Bo; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Transcription Factors

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

Dosage changes of a segment at 17p13.1 lead to intellectual disability and microcephaly as a result of complex genetic interaction of multiple genes. - Carvalho, Claudia M B; Vasanth, Shivakumar; Shinawi, Marwan; Russell, Chad; Ramocki, Melissa B; Brown, Chester W; Graakjaer, Jesper; Skytte, Anne-Bine; Vianna-Morgante, Angela M; Krepischi, Ana C V; Patel, Gayle S; Immken, LaDonna; et al. (Am J Hum Genet, 2014)
The 17p13.1 microdeletion syndrome is a recently described genomic disorder with a core clinical phenotype of intellectual disability, poor to absent speech, dysmorphic features, and a constellation of more variable clinical features, most prominently microcephaly. We identified five subjects with copy-number variants (CNVs) on 17p13.1 for whom we performed detailed clinical and molecular studies. Breakpoint mapping and retrospective analysis of published cases refined the smallest region of overlap (SRO) for microcephaly to a genomic interval containing nine genes. Dissection of this phenotype in zebrafish embryos revealed a complex genetic architecture: dosage perturbation of four genes (ASGR1, ACADVL, DVL2, and GABARAP) impeded neurodevelopment and decreased dosage of the same loci caused a reduced mitotic index in vitro. Moreover, epistatic analyses in vivo showed that dosage perturbations of discrete gene pairings induce microcephaly. Taken together, these studies support a model in which concomitant dosage perturbation of multiple genes within the CNV drive the microcephaly and possibly other neurodevelopmental phenotypes associated with rearrangements in the 17p13.1 SRO.
Keywords: Abnormalities, Multiple; Acyl-CoA Dehydrogenase, Long-Chain; Adaptor Proteins, Signal Transducing; Animals; Asialoglycoprotein Receptor; Base Sequence; Cell Line; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human, Pair 17; Dishevelled Proteins; Flow Cytometry; Gene Dosage; Humans; Immunohistochemistry; Intellectual Disability; Microcephaly; Microtubule-Associated Proteins; Molecular Sequence Data; Phosphoproteins; Retrospective Studies; Sequence Analysis, DNA; Smith-Magenis Syndrome; Syndrome; Zebrafish

Exome sequencing identifies a recurrent de novo ZSWIM6 mutation associated with acromelic frontonasal dysostosis. - Smith, Joshua D; Hing, Anne V; Clarke, Christine M; Johnson, Nathan M; Perez, Francisco A; Park, Sarah S; Horst, Jeremy A; Mecham, Brig; Maves, Lisa; Nickerson, Deborah A; Cunningham, Michael L (Am J Hum Genet, 2014)
Acromelic frontonasal dysostosis (AFND) is a rare disorder characterized by distinct craniofacial, brain, and limb malformations, including frontonasal dysplasia, interhemispheric lipoma, agenesis of the corpus callosum, tibial hemimelia, preaxial polydactyly of the feet, and intellectual disability. Exome sequencing of one trio and two unrelated probands revealed the same heterozygous variant (c.3487C>T [p. Arg1163Trp]) in a highly conserved protein domain of ZSWIM6; this variant has not been seen in the 1000 Genomes data, dbSNP, or the Exome Sequencing Project. Sanger validation of the three trios confirmed that the variant was de novo and was also present in a fourth isolated proband. In situ hybridization of early zebrafish embryos at 24 hr postfertilization (hpf) demonstrated telencephalic expression of zswim6 and onset of midbrain, hindbrain, and retinal expression at 48 hpf. Immunohistochemistry of later-stage mouse embryos demonstrated tissue-specific expression in the derivatives of all three germ layers. qRT-PCR expression analysis of osteoblast and fibroblast cell lines available from two probands was suggestive of Hedgehog pathway activation, indicating that the ZSWIM6 mutation associated with AFND may lead to the craniofacial, brain and limb malformations through the disruption of Hedgehog signaling.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Craniofacial Abnormalities; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Face; Hedgehog Proteins; Humans; Intellectual Disability; Limb Deformities, Congenital; Mandibulofacial Dysostosis; Mice; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Zebrafish; Zinc Fingers

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors

Mutations in CSPP1 lead to classical Joubert syndrome. - Akizu, Naiara; Silhavy, Jennifer L; Rosti, Rasim Ozgur; Scott, Eric; Fenstermaker, Ali G; Schroth, Jana; Zaki, Maha S; Sanchez, Henry; Gupta, Neerja; Kabra, Madhulika; Kara, Majdi; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2014)
Joubert syndrome and related disorders (JSRDs) are genetically heterogeneous and characterized by a distinctive mid-hindbrain malformation. Causative mutations lead to primary cilia dysfunction, which often results in variable involvement of other organs such as the liver, retina, and kidney. We identified predicted null mutations in CSPP1 in six individuals affected by classical JSRDs. CSPP1 encodes a protein localized to centrosomes and spindle poles, as well as to the primary cilium. Despite the known interaction between CSPP1 and nephronophthisis-associated proteins, none of the affected individuals in our cohort presented with kidney disease, and further, screening of a large cohort of individuals with nephronophthisis demonstrated no mutations. CSPP1 is broadly expressed in neural tissue, and its encoded protein localizes to the primary cilium in an in vitro model of human neurogenesis. Here, we show abrogated protein levels and ciliogenesis in affected fibroblasts. Our data thus suggest that CSPP1 is involved in neural-specific functions of primary cilia.
Keywords: Abnormalities, Multiple; Brain; Cell Cycle Proteins; Centrosome; Cerebellar Diseases; Cerebellum; Cilia; Cohort Studies; Eye Abnormalities; Fibroblasts; Gene Deletion; Humans; Image Processing, Computer-Assisted; Kidney Diseases, Cystic; Microtubule-Associated Proteins; Polymorphism, Single Nucleotide; Retina

Mutations in PIEZO2 cause Gordon syndrome, Marden-Walker syndrome, and distal arthrogryposis type 5. - McMillin, Margaret J; Beck, Anita E; Chong, Jessica X; Shively, Kathryn M; Buckingham, Kati J; Gildersleeve, Heidi I S; Aracena, Mariana I; Aylsworth, Arthur S; Bitoun, Pierre; Carey, John C; Clericuzio, Carol L; Crow, Yanick J; et al. (Am J Hum Genet, 2014)
Gordon syndrome (GS), or distal arthrogryposis type 3, is a rare, autosomal-dominant disorder characterized by cleft palate and congenital contractures of the hands and feet. Exome sequencing of five GS-affected families identified mutations in piezo-type mechanosensitive ion channel component 2 (PIEZO2) in each family. Sanger sequencing revealed PIEZO2 mutations in five of seven additional families studied (for a total of 10/12 [83%] individuals), and nine families had an identical c.8057G>A (p.Arg2686His) mutation. The phenotype of GS overlaps with distal arthrogryposis type 5 (DA5) and Marden-Walker syndrome (MWS). Using molecular inversion probes for targeted sequencing to screen PIEZO2, we found mutations in 24/29 (82%) DA5-affected families and one of two MWS-affected families. The presence of cleft palate was significantly associated with c.8057G>A (Fisher's exact test, adjusted p value < 0.0001). Collectively, although GS, DA5, and MWS have traditionally been considered separate disorders, our findings indicate that they are etiologically related and perhaps represent variable expressivity of the same condition.
Keywords: Abnormalities, Multiple; Arachnodactyly; Arthrogryposis; Blepharophimosis; Child; Child, Preschool; Cleft Palate; Clubfoot; Connective Tissue Diseases; Contracture; Exome; Female; Hand Deformities, Congenital; Humans; Ion Channels; Male; Mutation; Ophthalmoplegia; Pedigree; Retinal Diseases

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Neonatal diabetes, gallbladder agenesis, duodenal atresia, and intestinal malrotation caused by a novel homozygous mutation in RFX6. - Concepcion, Jennifer P; Reh, Christina S; Daniels, Mark; Liu, Xiaoming; Paz, Veronica P; Ye, Honggang; Highland, Heather M; Hanis, Craig L; Greeley, Siri Atma W (Pediatr Diabetes, 2014)
Recently, bi-allelic mutations in the transcription factor RFX6 were described as the cause of a rare condition characterized by neonatal diabetes with pancreatic and biliary hypoplasia and duodenal/jejunal atresia. A male infant developed severe hyperglycemia (446 mg/dL) within 24 h of birth. Acute abdominal concerns by day five necessitated exploratory surgery that revealed duodenal atresia, gallbladder agenesis, annular pancreas and intestinal malrotation. He also exhibited chronic diarrhea and feeding intolerance, cholestatic jaundice, and subsequent liver failure. He died of sepsis at four months old while awaiting liver transplantation. The phenotype of neonatal diabetes with intestinal atresia and biliary agenesis clearly pointed to RFX6 as the causative gene; indeed, whole exome sequencing revealed a novel homozygous RFX6 mutation c.779A>C; p.Lys260Thr (K260T). This missense mutation also changes the consensus 5' splice donor site before intron 7 and is thus predicted to cause disruption in splicing. Both parents, who were not known to be related, were heterozygous carriers. Targeted genetic testing based on consideration of phenotypic features may reveal a cause among the many genes now associated with heterogeneous forms of monogenic neonatal diabetes. Our study demonstrates the feasibility of using modern sequencing technology to identify one such rare cause. Continued research is needed to determine the possible cost-effectiveness of this approach, especially when clear phenotypic clues are absent. Further study of patients with RFX6 mutations should clarify its role in pancreatic, intestinal and enteroendocrine cellular development and explain features such as the diarrhea exhibited in our case.
Keywords: Abnormalities, Multiple; Congenital Abnormalities; Diabetes Mellitus, Type 1; Digestive System Abnormalities; DNA-Binding Proteins; Duodenal Obstruction; Fatal Outcome; Gallbladder; Humans; Infant; Infant, Newborn; Infant, Newborn, Diseases; Intestinal Atresia; Intestinal Volvulus; Male; Pancreas; Pancreatic Diseases; Regulatory Factor X Transcription Factors; Transcription Factors

Sclerocornea in a patient with van den Ende-Gupta syndrome homozygous for a SCARF2 microdeletion. - Migliavacca, Michele P; Sobreira, Nara L M; Antonialli, Graziela P M; Oliveira, Mariana M; Melaragno, Maria Isabel S A; Casteels, Ingele; de Ravel, Thomy; Brunoni, Decio; Valle, David; Perez, Ana Beatriz A (Am J Med Genet A, 2014)
Van den Ende-Gupta Syndrome (VDEGS) is an autosomal recessive disorder characterized by blepharophimosis, distinctive nose, hypoplastic maxilla, and skeletal abnormalities. Using homozygosity mapping in four VDEGS patients from three consanguineous families, Anastacio et al. [Anastacio et al. (2010); Am J Hum Genet 87:553-559] identified homozygous mutations in SCARF2, located at 22q11.2. Bedeschi et al. [2010] described a VDEGS patient with sclerocornea and cataracts with compound heterozygosity for the common 22q11.2 microdeletion and a hemizygous SCARF2 mutation. Because sclerocornea had been described in DiGeorge-velo-cardio-facial syndrome but not in VDEGS, they suggested that the ocular abnormalities were caused by the 22q11.2 microdeletion. We report on a 23-year-old male who presented with bilateral sclerocornea and the VDGEGS phenotype who was subsequently found to be homozygous for a 17 bp deletion in exon 4 of SCARF2. The occurrence of bilateral sclerocornea in our patient together with that of Bedeschi et al., suggests that the full VDEGS phenotype may include sclerocornea resulting from homozygosity or compound heterozygosity for loss of function variants in SCARF2.
Keywords: Abnormalities, Multiple; Adult; Arachnodactyly; Blepharophimosis; Bone and Bones; Chromosomes, Human, Pair 22; Contracture; Cornea; Corneal Diseases; Exons; Facies; Hand Deformities, Congenital; Homozygote; Humans; Male; Phenotype; Radiography; Scavenger Receptors, Class F; Sequence Analysis, DNA; Sequence Deletion; Young Adult

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Muzny, Donna M; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Gibbs, Richard A; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Whole-exome sequencing identified a patient with TMCO1 defect syndrome and expands the phenotic spectrum. - Caglayan, A O; Per, H; Akgumus, G; Gumus, H; Baranoski, J; Canpolat, M; Calik, M; Yikilmaz, A; Bilguvar, K; Kumandas, S; Gunel, M (Clin Genet, 2013)
Keywords: Abnormalities, Multiple; Base Sequence; Child; Consanguinity; Exome; Humans; Male; Membrane Proteins; Pedigree; Phenotype; Sequence Analysis, DNA; Syndrome